2016
DOI: 10.1007/978-1-4939-3023-4_49
|View full text |Cite
|
Sign up to set email alerts
|

Local Measurement of Flap Oxygen Saturation: An Application of Visible Light Spectroscopy

Abstract: The aim was to develop and test a new device (OxyVLS) to measure tissue oxygen saturation by visible light spectroscopy independently of the optical pathlength and scattering. Its local applicability provides the possibility of real time application in flap reconstruction surgery. We tested OxyVLS in a liquid phantom with optical properties similar to human tissue. Our results were in good agreement with a conventional near infrared spectroscopy device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Spectra were acquired every 12s. Based on VLS it is possible to determine the StO 2 [28]. Here we applied an improved method to measure StO 2 .…”
Section: Nirs Oximeters Smentioning
confidence: 99%
See 2 more Smart Citations
“…Spectra were acquired every 12s. Based on VLS it is possible to determine the StO 2 [28]. Here we applied an improved method to measure StO 2 .…”
Section: Nirs Oximeters Smentioning
confidence: 99%
“…Here we applied an improved method to measure StO 2 . The wavelength range, from 520nm to 600nm, is remarkable by oxyhemoglobin (O 2 Hb) having two peaks (λ = 542nm and λ = 577nm, data from [40]) and deoxyhemoglobin (HHb) having only one peak (λ = 556nm, data from [40]) [28]. Calculating StO 2 based on the distance between the peaks as described in [28] is prone to errors.…”
Section: Nirs Oximeters Smentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a high correlation ( r > 0.94) but also high variation of up to 33.5% between different algorithms and co‐oximetry . We recently introduced an oximeter (OxyVLS) based on the algorithm introduced by Wodick and Lübbers and tested it in standard liquid phantoms, simulating human tissue . We concluded that the ability of OxyVLS to measure StO 2 was in good agreement with frequency domain NIRS oximeters and independent of total hemoglobin concentration ([tHb]) and μs.…”
Section: Introductionmentioning
confidence: 83%
“…An example of this would be measuring flaps, in the operation theater, after anastomosis and measuring the heart. In such scenarios, diffusive reflective visible light spectroscopy (VLS) is beneficial because it provides local quantification of absolute StO 2 with no assumption as to the tissue geometry and the absolute value of reduced scattering coefficient (μs) . To date several algorithms have been introduced to measure absolute StO 2 based on VLS.…”
Section: Introductionmentioning
confidence: 99%